Implementasi Teori Mashlahah Mulghah Najmuddin ath-Thufi (Analisis Terhadap Q.S. Al-Maidah [5]: 5 dan Q.S. Al-Baqarah [2]: 221 tentang Hukum Nikah Beda Agama) - Muhammad Asadurrohman; Alamsyah; Maimun; Muhammad Latif Mukti; Asadurrohman, Muhammad (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2025)
Abstract The Maṣlaḥa Mulgha theory developed by Najmuddin al-Ṭūfī is one theory that to this day is considered controversial. At first glance, this theory seems to negate stipulations explained by the text (naṣṣ) in order to uphold truth sourced from the intellect of scholars. Nevertheless, in Indonesia, there are several legal provisions that indirectly reflect the application of al-Ṭūfī’s theory, one of which is the prohibition of interfaith marriage as regulated and reinforced through the interpretation of Q.S. al-Māidah [5]: 5 and Q.S. al-Baqarah [2]: 221. This research aims to examine the existence of al-Ṭūfī's theory and link it to the provisions prohibiting interfaith marriage in Indonesia, with the hope of providing an understanding of its relevance in the process of Islamic legal discovery. This research uses the library research method with the collection of primary, secondary, and tertiary data. The results show that the Mashlahah Mulghah theory can be one option in answering contemporary legal issues that emerge and develop complexly. Thus, the prohibition of interfaith marriage in Indonesia has significant relevance to the application of the Maṣlaḥa Mulgha theory in an applicative and solutive manner. Keywords: Al-Ṭūfi; Indonesia; Marriage; Maṣlaḥa Mulgha; Religious Difference.